ANALISIS RASIO PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA CV PANEN JAYA - Baharuddin, Muhammad Rezha; Idris, Hariany; Samsinar, Samsinar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Thisl study aimsl to determinel the financial performance ofl CV Panen Jaya during the l2017 – 2021 periodl using the financial ratio lmethod, namely the profitability ratio. Thel variables ofl this study arel the financial statements for 2017 – 2021 as a variable (Xl) which isl referred tol as thel independent lvariable, and financial performance as a variable (Yl) which isl referred tol as thel dependent lvariable. The populationl of this study is the financial statements of CV Panen Jaya, while the sample uses financial reports consisting of income statements and balance sheets at CV Panen Jaya for the period 2017 - 2021. Datal collection isl carried outl using thel documentation lmethod. Datal analysis wasl performed with descriptivel analysis. Thel results ofl this studyl indicate thatl the profitability ratios in the 2017 – 2021 period canl be saidl to bel good becausel the companyl has a liquid financial condition. Basedl on thel results ofl calculating profitability ratios (Net Profitl Margin, Return On Assets) inl the period 2017 - 2021 the financial performance of CV Panen Jaya is considered good where each ratio value isl above thel average industry standard profitabilityl ratio value. Meanwhile, Returnl On Equity is considered unfavorable where each ratio value isl below thel industry averagel profitability ratio